Impact of ascending aortic, hemiarch and arch repair on early and long-term outcomes in patients with Stanford A acute aortic dissection. (December 2018) - Merkle, Julia; Sabashnikov, Anton; Deppe, Antje-Christin; Zeriouh, Mohamed; Maier, Johanna; Weber, Carolyn; Eghbalzadeh, Kaveh; Schlachtenberger, Georg; Shostak, Olga; Djordjevic, Ilija; Kuhn, Elmar; Rahmanian, Parwis B.; et al.
Background: Stanford A acute aortic dissection (AAD) is a life-threatening emergency associated with major morbidity and mortality. The aim of this study was to compare outcomes of three different surgical approaches in patients with Stanford A AAD. Methods: From January 2006 to March 2015 a total of 240 consecutive patients with diagnosed Stanford A AAD underwent elective, isolated surgical aortic repair in our centre. Patients were divided into three groups according to the extent of surgical repair: isolated replacement of the ascending aorta, hemiarch replacement and total arch replacement. Patients were followed up for up to 9 years. After univariate analysis multinomial logistic regression was performed for subgroup analysis. Baseline characteristics and endpoints as well as long-term survival were analysed. Results: There were no statistically significant differences among the three groups in terms of demographics and preoperative baseline and clinical characteristics. Incidence of in-hospital stroke ( p = 0.034), need for reopening due to bleeding ( p = 0.031) and in-hospital mortality ( p = 0.017) increased significantly with the extent of the surgical approach. There was no statistical difference in terms of long-term survival ( p = 0.166) among the three groups. Applying multinomial logistic regression for subgroup analysis significantly higher odds for stroke ( p = 0.023), reopening for bleeding ( p = 0.010) and in-hospital mortality ( p = 0.009) for the arch surgery group in comparison to the ascending aorta surgery group as well as significantly higher odds for stroke ( p = 0.029) for the total arch surgery group in comparison to the hemiarch surgery group were identified. Conclusions: With Stanford A AAD the incidence of perioperative complications increased significantly with the extent of the surgical approach. Subgroup analysis and long-term follow up in patients undergoing isolated ascending or hemiarch surgery showed a lower incidence of cerebrovascular events compared with surgery for total arch replacement.